Cloud Technologies in Healthcare : Transforming Patient Care and Clinical Outcomes - Anshul Goel (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
This comprehensive article examines the transformative impact of cloud technologies on modern healthcare delivery systems, focusing on their role in revolutionizing patient care, clinical decision-making, and healthcare management. The article analyzes the multifaceted implementation of cloud-based solutions across various healthcare domains, including electronic health records management, telemedicine services, artificial intelligence integration, and clinical research platforms. Through detailed examination of cloud-based healthcare infrastructure, the research highlights significant advancements in remote access systems, data analytics capabilities, and medical imaging solutions that have enhanced healthcare delivery efficiency and accessibility. The investigation extends to advanced technology integration, emphasizing the crucial role of artificial intelligence in predictive analytics, diagnostic assistance, and treatment optimization, while also exploring the evolution of patient engagement through sophisticated portal systems and personalized care delivery approaches. Results indicate that cloud technologies have substantially improved healthcare outcomes through enhanced data accessibility, streamlined clinical workflows, and improved patient engagement, despite persistent challenges in security, interoperability, and implementation costs. The article demonstrate the pivotal role of cloud computing in shaping the future of healthcare delivery, particularly in enabling personalized medicine approaches and expanding access to quality healthcare services across diverse geographical and socioeconomic boundaries.